The Influence of Heat Treatment and Quencing Media at Bronze 80% Cu–20% Sn toward Fatique Life - Anak Agung Istri Agung Sri Komaladewi; I Ketut Suarsana (Jurnal Energi Dan Manufaktur, 2009)
Production of the Balinese gamelan product rest on molding process which then continued with forging process, adjustment,and finally the finishing process. But still often to make the failure from this material like. The material become brokebecause heavy thing with the user processing (playing gambelan) with continuity in the long time. The broke that happenfrom the heavy thing by the continuety that is called fatigue. At this examination the things that will be up is how much theheat treatment influence and the cooler thing with the fatigue life through the Reversed Bending process. By to variated theheat treatment and cooler thing to Bronze mixture 80%Cu and 20%Sn. This examination to aim at knowing the heattreatment influence and cooler thing at the composition of Bronze 80%Cu and 20%Sn about the fatigue life.The makingprocess of this things made by copper solution and the white Tin with the composition are 80%Cu and 20%Sn by variatedheat treatment and cooler media. The produce of this solution will print with the Reversed Bending speciment. Then thespeciment gift the heat treatment about 6500 C, 7000 C till 7500 C, and then the speciment keep cold by the water, oil and theair. The thing will be analize from the breach counture, Macro Structure and Micro Structure.The examination produceshowing the growing up at the fatigue life in the Bronze mixture 80%Cu - 20%Sn, From the heat treatment 6500 C, 7000 Cand 7500 C and become the drop age fatigue with the water cooler media with the age fatigue abaut 36621 cycle, and thefatigue by oil about 44975 cycle and the air cooler age fatigue about 55191 cycle. The inspection makro structure thebreach face colouring litle bit dark and the inspection mikro structure, the metal structure lool more bright.